Characterization and catalytic activity of zirconium dioxide prepared by sol-gel - Davies, Lilian Emilia (2005)
Zirconia samples prepared from Zr(n-OC3H7)4 and ZrOCl2 were characterized by XRD,BET surface area, TG-DTA, TEM/SEM, FTIR, and D2O exchange. Oxides obtained from the alkoxide contain two types of hydroxyl groups at 3704 and 3597 cm-1, which do not exchange with D2O. Those obtained from ZrOCl2 produced three types of hydroxyl groups at 3774, 3733 and 3671 cm-1, which do exchange with D2O. Surface acidity was determined by FTIR of adsorbed lutidine. Only Lewis acid sites were found on samples from ZrOCl2 hydrolysis. FTIR spectra of calcined samples exhibited strong absorption bands in the 1800 to 1000 cm-1 region,which are ascribed to various types of carbonate and bicarbonate species. These ones are strongly adsorbed on the surface oxide and they are removed only after 3 hours at 600 ºC in stream of H2. Samples derive from the alkoxide precursor restore the original carbonate species after exposure to O2 at 600ºC. Catalytic activity for i-propanol dehydration/dehydrogenation showed the absence of basic centers and an intermediate dehydration activity between that of silica and alumina.